Strategies and mechanisms for mainstreaming climate change into agriculture and irrigation sector reforms - Rana, Abdul Wajid (International Food Policy Research Institute, 2019)
Global warming is unequivocal, and since 1950s, many of the observed changes are unprecedented over decades to millennia. The atmosphere has warmed (0.85oC over the period 1883 to 2012). Glaciers have continued to shrink almost worldwide. The amounts of snow and ice have diminished. The Greenland and Antarctic ice sheets have been losing mass. The sea level has risen and on a global scale, the ocean warming is largest near the surface, and the upper 75 m warmed by 0.11°C per decade over the period 1971 to 2010. The increase in greenhouse gas (GHG) emissions, driven largely by economic and population growth, together with other anthropological drivers have caused changes in climate system. Continued emission of greenhouse gases is expected to cause further warming and changes in the climate system increasing the possibilities of severe and irreversible impacts for people and ecosystem. Surface temperature is projected to rise over the 21st century (0.3 to 1.7oC) and it is likely that heat waves will occur more frequently and last longer. The global ocean will continue to warm during the 21st century, with the strongest warming projected for the surface in tropical and Northern Hemisphere subtropical regions. The global glacier volume excluding glaciers on the periphery of Antarctica (and excluding the Greenland and Antarctic ice sheets) is projected to decrease by 15 to 55%.1 Therefore, limiting climate change would need substantial and sustained reduction in greenhouse gas emissions through adaptation and mitigation strategies. These include innovation and investment in environmentally sound technologies and infrastructure, sustainable livelihoods and behavioural and lifestyles choices as well as effective institutions and governance.